1997
DOI: 10.1016/s0924-9338(97)80002-8
|View full text |Cite
|
Sign up to set email alerts
|

Two types classification of male alcoholism confirmed

Abstract: SummaryIn recent years a two types classification of male alcoholism has been proposed by several authors. The study aimed at a testing of type I/type II classification of alcoholism in an independent sample. A total of 351 Research Diagnostic Criteria (RDC) male alcoholics consecutively admitted for an inpatient psychiatric treatment were studied. Type II characteristics were extracted from the pertinent literature; 19 available variables best representing these characteristics were selected. The data was col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 34 publications
2
8
0
Order By: Relevance
“…Cloninger used genetic epidemiological data to support a personality model that identified two subtypes of alcoholism. Type-I ADs (AD-Is) aggressiveness (e.g., Bjork, et al, 2004;Hallman, von Knorring, & Oreland, 1996;Modestin & Wurmle, 1997;L. von Knorring, von Knorring, Smigan, Lindberg, & et al, 1987).…”
Section: The Present Studymentioning
confidence: 99%
“…Cloninger used genetic epidemiological data to support a personality model that identified two subtypes of alcoholism. Type-I ADs (AD-Is) aggressiveness (e.g., Bjork, et al, 2004;Hallman, von Knorring, & Oreland, 1996;Modestin & Wurmle, 1997;L. von Knorring, von Knorring, Smigan, Lindberg, & et al, 1987).…”
Section: The Present Studymentioning
confidence: 99%
“…In sum, although a broad range of empirical research has supported the validity of multivariate ATs Modestin and Wurmle 1997), with studies suggesting a signifi cant overlap across classifi cations (Pombo and Lesch 2009), there remains a lack of consensus regarding their clinical implications. As some authors have mentioned, despite the theoretical and statistical value of these schemes, the clinical and research implications of this framework cannot be understood until adequate clinical testing has been carried out (Schuckit and Irwin 1989;Caetano 2004;Hesselbrock and Hesselbrock 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Since it has been shown that increased haemolysis and chronic anaemia accompany alcoholism and nonmetabolised ethanol could have direct effects on membrane properties, 7,41 an osmotic fragility test was performed on the erythrocytes of the study groups to evaluate the sensitivity of their erythrocytes toward hypotonic saline. Measurement of osmotic fragility provides a useful indicator as to whether a subject's erythrocytes are normal.…”
Section: Resultsmentioning
confidence: 99%
“…3,4 Although heterogeneity of the male inpatient population of alcoholics was demonstrated and the existence of broadly defined type I and II alcoholism was confirmed, additional criteria such as more discriminative biological markers are needed in order to determine novel medical strategies for the treatment of the alcoholic subgroups. [5][6][7] implicated in ethanol-induced oxidative tissue damage. [8][9][10][11][12] Although it is generally accepted that increased lipid peroxidation is a major pathogenetic mechanism in ethanol-induced hepatotoxicity, 13 it has been suggested that ethanol-induced lipid peroxidation also occurs in extrahepatic tissues.…”
Section: Introductionmentioning
confidence: 99%